Anxiety Level of University Students During COVID-19 in Saudi Arabia - Khoshaim, Heba Bakr; Al-Sukayt, Areej; Chinna, Karuthan; Nurunnabi, Mohammad; Sundarasen, Sheela; Kamaludin, Kamilah; Baloch, Gul Mohammad; Hossain, Syed Far Abid (Frontiers in Psychiatry, 2020)
COVID-19) is the worst pandemic of this millennium and it is considered to be the ‘public enemy number one’. This catastrophe has changed the way we live in the blink of an eye. Not only has it threatened our existence and health status but the damage associated with it could equally affect our economic, social, and educational systems. The focus of this study was on the anxiety level of university students during the COVID-19 pandemic in Saudi Arabia. The study was conducted between March and June 2020. A questionnaire was administered online and 400 completed questionnaires were returned. In this study, the Zung self-rating anxiety scale was used to determine the anxiety levels among the respondents. The results indicated that about 35% of the students experienced moderate to extreme levels of anxiety. Anxiety was highly associated with age, sex, and level of education. These findings can enlighten government agencies and policy makers on the importance of making prompt, effective decisions to address students’ anxiety during the COVID-19 pandemic. Researchers are encouraged to focus their future studies on how to develop strategies to boost students’ resilience and enhance their adaptability skills for similar disasters in the future.